2012
DOI: 10.1177/138826271201400201
|View full text |Cite
|
Sign up to set email alerts
|

Welfare as a Means for Political Stability: A Law and Society Analysis

Abstract: Welfare as a means for political stability : a law and society analysisSvensson, Måns; Urinboyev, Rustam; Åström, Karsten General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, Börjesson and Broady are also at pains to avoid clouding over important points of political consensus and deeper ideological agreement between the political parties. As is also suggested by Svensson, Urinboyev and Åström (2012), there was also a lot of agreement between the political parties regarding the development of an ostensibly open education system in Sweden in the 1940s. Sweden was a class-ridden society that had followed a very similar developmental trajectory to that of other Western countries and all parties were concerned about social stability and the possibility of using welfare reforms for addressing this (Nilsson Lindström and Beach, 2013;Svensson et al, 2012).…”
Section: Resonance In Political and Professional Resistance And Opposmentioning
confidence: 80%
See 2 more Smart Citations
“…However, Börjesson and Broady are also at pains to avoid clouding over important points of political consensus and deeper ideological agreement between the political parties. As is also suggested by Svensson, Urinboyev and Åström (2012), there was also a lot of agreement between the political parties regarding the development of an ostensibly open education system in Sweden in the 1940s. Sweden was a class-ridden society that had followed a very similar developmental trajectory to that of other Western countries and all parties were concerned about social stability and the possibility of using welfare reforms for addressing this (Nilsson Lindström and Beach, 2013;Svensson et al, 2012).…”
Section: Resonance In Political and Professional Resistance And Opposmentioning
confidence: 80%
“…Sweden was a class-ridden society that had followed a very similar developmental trajectory to that of other Western countries and all parties were concerned about social stability and the possibility of using welfare reforms for addressing this (Nilsson Lindström and Beach, 2013;Svensson et al, 2012). Thus whilst the school and teacher education reforms between the end of WW2 and the 1990s seemed to be promoted by the Social Democrats as a part of a welfare state project that other parties opposed, this is a truth with some modification (Beach, 2018;Börjesson and Broady, 2016;Svensson et al, 2012).…”
Section: Resonance In Political and Professional Resistance And Opposmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the method is concerned with distinguishing between the 'essential' attributes that lie in the nature of the norms (together they form the general deinition of the sociolegal concept of norms) and other 'accidental' attributes that are characteristic within certain groups of norms (such as social and legal norms). The result of this model for creating a deinition -and the actual deinition itself -has been tested in a number of research projects within SoL at Lund University (for example, Hydén and Svensson, 2008;Svensson, 2008;Baier and Svensson, 2009;Svensson andLarsson, 2009 andLeo, 2010;Hydén, 2011;Urinboyev, 2011;Larsson, 2011a;Naujėkaitė, 2011;Svensson and Urinboyev, 2012;Svensson et al, 2013;Leo and Wickenberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the policy level, the exchange scenario can take the form of programmatic redistribution. Researchers on welfare regime have suggested that, by offsetting the effects of poverty and inequality in society, access to public services and welfare benefits becomes a major means for addressing political and social instability (see for example, Svensson et al 2012). Enacting welfare policies can improve the living standards of citizens and co-opt the political opposition and therefore decrease the incentives for contentious mobilization.…”
mentioning
confidence: 99%